Screening insectary refugia plants that increase the performance of Diadegma semiclausum Hellen (Hymenoptera: Ichneumonidae) against diamondback moth larvae (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Asmoro PP, Dadang, Pudjianto, Winasa IW. 2021. Screening insectary refugia plants that increase the performance of Diadegma semiclausum Hellen (Hymenoptera: Ichneumonidae) against diamondback moth larvae. Biodiversitas 22: 4254-4260. Habitat manipulation through the planting of insectary refugia plants is one way of controlling pests. These refugia plants serve as the source of nutrients that improve the fitness of parasitoid against insect pests. In the cabbage agroecosystem, the presence of refugia plants is expected to benefit the parasitoid D. semiclausum. This study aimed to select insectary refugia plants beneficial for the D. semiclausum in term of attracting and increasing their longevity, and parasitization ability against P. xylostella larvae. Ten species of refugia plants were used in this study, i.e., Ageratum conyzoides, Galinsoga parviflora, Sphagneticola trilobata, Synedrella nodiflora, Portulaca oleracea, Rorippa indica, Brassica rapa, Apium graveolens, Ocimum basilicum, and Arachis pintoi. The methods used in this study included testing the response of the imago olfactory to refugia plants and its effect on the longevity and parasitization level. The results showed that of the ten species of investigated, R. indica and A. graveolens were the most attractive for the presence of parasitoids. The two refugia plants could also increase the longevity and parasitization rate compared to the water treatment. R. indica and A. graveolens are recommended as refuge plants in the cabbage agroecosystems to control P. xylostella.
Keywords: Biological control, habitat manipulation, insect olfactory, insectary plant, Plutella xylostella.